Whole exome sequencing analysis of cerebral palsy patients with underlying genetic factors - Azhar, Nur Atikah Nor (2021)
Cerebral palsy (CP) is a result of neurological dysfunctions that do not worsen with age but will be manifested as muscle impairments till adulthood. Some CP risk factors are intrauterine infection, brain malformation, instrumental delivery, etc. that occur at three different events (antenatal, intrapartum and postpartum). Meanwhile, idiopathic CP refers to CP cases with unknown risk factors. This exploratory study with no proposed hypothesis of specific loci was carried out to explore CP genetic in Kelantan patients with underlying genetic factors using Whole Exome Sequencing (WES). As opposed to other neurodevelopmental disabilities, contribution of genomic abnormalities to CP occurrence has not been extensively researched despite probably accounting for 70–80% of cases with prenatal causes. Plus, Malaysia has yet to establish CP prevalence and genetic database. Therefore, identification of genomic causes would improve CP causal insight in selected families. In total, 20 subjects consisting of 10 CP individuals and 10 unaffected parents were analysed in the current study. The sequenced DNA samples were analysed using bioinformatics Genome Analysis Toolkit (GATK) to generate all possible variants. We found 37 rare de novo (n=29) and inherited variants (n=8) from a total of 29 genes and classified them according to American College Medical Genetic (ACMG) standard guidelines. There are nine central nervous system (CNS) related genes (CDKL2, CEP164, FAM104B, FAM163A, FXR2, KCNK18, KCNQ3, MAPRE3 and RBMX, CP is a disorder of CNS origin and these genetic mutations are anticipated to contribute to CNS defect. Nine mutated immune-related genes (COL6A6, COL7A1, CYHR1, DLL1, GPR97, HLA DRB1, HLA-DRB5, LYST and MUC16) are present in CP subjects only, which possibly indicates that CP individuals may have potential of developing immune-related problems. Thus, CP may be categorized as immune dysregulation-related neurological disorder. Next are three potentially immune-related mutated genes (ANKRD36, DNAH17 and TTC13) with unknown molecular function, but are associated with the immune system. There are also eight mutated genes of other categories (ANO5, ASTE1 BEST3, CTBP2 CTDSP2, DCHS2, GLYR1 and KRTAP19-6). Based on the variant data we hypothesize that familial genetic CP is genetically heterogenous, consisting of discovered de novo and inherited variants that may contain important predictive information on CP. This encourages future studies with bigger sample size, more validation analysis and functional characterization to further understand the contribution of the related genes to CP. This could help in the future development of molecular targeted drugs and CP therapeutics intervention.